Desmethylbellidifolin From Gentianella acuta Ameliorate TNBS-Induced Ulcerative Colitis Through Antispasmodic Effect and Anti-Inflammation - Ni, Yajuan; Liu, Mengyang; Yu, Haiyang; Chen, Yue; Liu, Yanxia; Chen, Suyile; Ruan, Jingya; Da, Alatengchulu; Zhang, Yi; Wang, Tao (Frontiers in Pharmacology, 2019)
Desmethylbellidifolin (DMB) is a natural xanthone extracted from Gentianella acuta, which is used as the anti-diarrhea drug in Traditional Mongolian Medicines. It remains unknown whether DMB can ameliorate ulcerative colitis (UC). In this study, Trinitrobenzenesulfonic acid (TNBS)-induced colitis rats were treated with Gentianella acuta extract (GAE) or DMB for 10 days. Body weight, food and water intake, rectal bleeding score, diarrhea score and histopathological parameters were measured. Rat colon were collected to determine myeloperoxidase, nitric oxide levels and inflammatory cytokines expression. Additionally, role of DMB on lipopolysaccharide (LPS) stimulated RAW264.7 cell inflammatory response and intestine smooth muscle contraction were determined. The results showed that GAE and DMB treatment could significantly alleviate TNBS-induced UC. Colon morphological alteration, nitric oxide level and inflammatory cytokines level, such as nitric oxide synthase (iNOS), interleukin-6 (IL-6), tumor necrosis factor-a(TNF-a and cyclooxygenase-2 (COX-2), were decreased. In addition, DMB attenuated LPS induced nitric oxide release and pro-inflammatory cytokines expression in RAW264.7 cells. In mice isolated intestinal tissue, DMB also reduced the intestine smooth muscle spontaneous contraction, and inhibited KCl, acetylcholine, BaCl2 or histamine induced intestine smooth muscle active tension, while the active frequency was unaffected. Our results demonstrated that GAE and its active constituent DMB could inhibit TNBS-induced UC, reducing inflammatory response and alleviate colon muscle spasm. Suggesting DMB may be a good candidate for subsequent development as a multi-targeting drug for UC treatment.